Researches of the Figure Tamburlaine in English and Uzbek Literature (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is about the study of the image of great commander-in-chief Amir Temur (in English literature Tamburlaine), one of the famous person who built a fair and reasonable policy, religious tolerance, a centralized state in the Uzbek nation and literature and historiography, as an artistic image of the historical figure. It is also scientifically studied that Uzbek, English literary scholars and writers interpret this person in their historical and scientific works